2016
DOI: 10.3727/109830416x14655571061674
|View full text |Cite
|
Sign up to set email alerts
|

Cruise Tourist Dress Behaviors and Local–guest Reactions in a Muslim Country

Abstract: This article examines the ethics of tourism and cross-cultural communication between Western tourists and the local community in a Muslim country. Communicating with people who have different value systems and communication styles can contribute to various "culture shock situations" and to an increase in stereotypes and "stigma." The main goal of this research is to analyze the dress behavior of cruise tourists, applying the concept of "mindfulness" and secondly to analyze the voices and values of the residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This would require a slower mode of travel, involving more time, money and resources as well as more active involvement of the local community. Given the large number of cruise tourists, an enclosed ‘tourist bubble’ may relieve social pressure from the host community and their culture (Gutberlet, 2016a; Williams and Lew, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This would require a slower mode of travel, involving more time, money and resources as well as more active involvement of the local community. Given the large number of cruise tourists, an enclosed ‘tourist bubble’ may relieve social pressure from the host community and their culture (Gutberlet, 2016a; Williams and Lew, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This research is part of an extensive field-study in two tourist attractions in Oman, one urban attraction in Muscat and one in the periphery, examining the construction of space, tourist experiences and sociocultural impacts (Gutberlet, 2016a(Gutberlet, , 2016b(Gutberlet, , 2017(Gutberlet, , 2019. Qualitative methods including participant observation, travel ethnography, photography and in-depth interviews were conducted during nine cruise excursions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have, indeed, identified specific cultural aspects of Muslim-majority countries to which non-Muslim tourists often struggle to adapt. These include, inter alia, gender roles, dress codes, modes of greeting, the consumption of food and drink (including the taking of alcohol), gambling and bargaining conventions (Brown and Osman, 2017;Ghaderi et al, 2020;Gutberlet, 2016;Henderson, 2003). While these cultural aspects have been identified, however, it is acknowledged that more sophisticated research is needed to understand them more fully (Reisinger and Moufakkir (2015).…”
Section: Cultural Expectations In Muslim-majority Countriesmentioning
confidence: 99%